The History of astronomy (Mandaluyong City Exclusive distributor High Access Line Phils. Corp.)
From the megalithic observatory of Stonehenge, England, to modern times. How the circumference of the earth was measured seventeen hundred years before Columbus set sail. The evolution of early theories.
Narrator: Kerry Frumkin.
Keywords: Astronomy -- History